ANALISIS DAYA LAYAN DAN EFEKTIFITAS LOKASI PUSKEMAS DI KABUPATEN PATI - Yulianto, Rizki; Hayati, Rahma; Aji, Ananto (Geo-Image, 2016)
This study aims to determine (1) the pattern of the spatial distribution of Puskesmas in the district of Pati. (2) power serviceability Puskesmas in the district of Pati. (3) the effectiveness of the Puskesmas locations in Pati regency.The results of this study show the spatial distribution pattern of the Puskesmas in the Pati regency have a uniform pattern with a value of T = 1.26. Power serviceability berfariasi health centers in Pati regency. Power serviceability PHC facilities that include a lower value <1 which is in District Sukolilo, Kayen, Jaken, Bars, Juwana, Pati, Margorejo, Trangkil, and Dukuhseti. Power serviceability PHC facilities that include high-power value serviceability> 1 which is in District Winong, Pucakwangi and Gabus. While power serviceability facilities including health centers moderately intellectually power value = 1 which is in District Tambakromo, Jakenan, Gembong, Wedarijaksa, Margoyoso, Cluwak and Tayu. The level of public satisfaction with the services at the health facilities obtained level of community satisfaction index of 91.74, which means people feel very satisfied with the services available health facilities.